Penyalahgunaan Ayat Al-Quran dan Hadis oleh Golongan Agnostik dalam Persoalan Akidah: Abuse of Quran Verses and Hadith by Agnostic Groups in Questions of Faith - Talip, Farah Hanie; Kamarzaman, Mohd Haidhar; Ibrahim, Mazlan (Jurnal Usuluddin, 2023)
In recent times, there has been an increasing rejection of faith and indoctrination in religion. Agnostic beliefs are among the ideologies that seek to liberate the human mind from any assumptions about God. What misleads them is when they make objections to the primary sources of reference for the Islamic community, al-Quran and hadith, which ultimately result in misunderstandings in understanding the main sources of Islam. Therefore, the purpose of this article is to study the issues of misuse of Quranic verses and hadith and the distorted interpretations by the agnostic group in matters of faith. This study uses a qualitative research design using document analysis, comparative analysis, and historical analysis approaches. The writings of the agnostic group in mass media such as articles, magazines and newspapers related to the misuse of Quranic verses and hadith in matters of faith are examined and analysed. The findings of the study reveal that the confusion and misunderstandings of the agnostic group regarding Quranic verses and hadith are caused by various factors, including an excessive reliance on logical reasoning, a lack of proper understanding of faith, misconceptions about contextual and textual approaches, and the use of hermeneutical methods in interpreting Quranic verses and hadith.